China’s Policy in Refusing North Korea Nuclear Proliferation - Sulaiman, Vera Zerlinda Alamsyah (UI Scholars Hub, 2020)
This paper explains the main factors underlying China's policy of refusing North Korea's nuclear proliferation, whereas the two countries have established defense alliance relations since the breakup of the Korean War. Geopolitically, North Korea is a strategic country for China in the East Asian region, and both countries view the presence of the US military in the region as a threat. Subsequently, North Korea began to develop its nuclear capability to challenge the continuous US military presence in South Korea. Although China and North Korea see the US influence as a security threat, China maintains its position of refusing North Korea nuclear proliferation. Previous studies regarding the relations between the two countries have explained the factors that underlie China's refusal of North Korea's nuclear proliferation. However, there have been no studies that precisely portray how nuclear weapons can influence China's policy-making towards its allies. By using extended deterrence perspective, this paper explains the variables that influence China's rejection of North Korea's nuclear proliferation. The main argument in this study is that China refuses North Korea's nuclear proliferation as a result of the disadvantage if North Korea continues its nuclear proliferation and the impact towards the regional stability that is unfavorable to China.